Exploration of Mothers’ Perceptions and Barriers in Stunting Prevention: A Phenomenological Study of Families with Stunted Toddlers - Ruminta Sirait; Nilawati; Marta Imelda Br Sianturi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Stunting remains a significant public health challenge in Indonesia, particularly in Aceh Province, which recorded a prevalence of 28.6% in 2024. This study employs a descriptive phenomenological approach to explore maternal perceptions and barriers toward stunting prevention in Gele Lah Village, Central Aceh Regency. Data were collected through in-depth interviews, participant observation, and secondary document reviews involving eight primary informants and two key informants between January and February 2025, with analysis conducted using the Colaizzi method. The findings identified eight stunted toddlers and revealed primary barriers including the normalization of the condition through genetic attribution, social stigma associated with the stunting label, the practice of feeding "bu pisang" before six months of age, economic constraints, and poor sanitation; notably, one concrete case of an intergenerational malnutrition cycle was also identified. Effective interventions require culturally sensitive communication, the integration of local wisdom, the strengthening of the DASHAT program, and holistic assistance for at-risk families. Study limitations include limited transferability, a small informant sample, and reliance on secondary anthropometric data. Future research is recommended to utilize a broader mixed-methods design that incorporates paternal perspectives and standardized primary anthropometric measurements.